Two patterns of anterior insular cortex functional connectivity in bipolar disorder and schizophrenia. (15th November 2018) - Li, Jian; Tang, Yanqing; Womer, Fay; Fan, Guoguang; Zhou, Qian; Sun, Wenge; Xu, Ke; Wang, Fei
Abstract: Objectives: Bipolar disorder (BD) and schizophrenia (SZ) share structural abnormalities in the anterior insula cortex (AIC). The AIC appears to have a crucial role in emotional processing and regulation and cognitive control in BD and SZ. Methods: Forty-six participants with BD, 68 with SZ and 66 healthy controls (HC) underwent functional magnetic resonance imaging scanning. Resting-state functional connectivity (rsFC) from AIC subregions (ventral and dorsal) was compared among the three groups. Results: Compared to HC group, both BD and SZ groups exhibited increased rsFC from the ventral AIC (vAIC) and dorsal AIC (dAIC) to bilateral frontal pole and thalamus, the left middle frontal gyrus and the hippocampus. Meanwhile, the BD group demonstrated increased rsFC from the vAIC to the perigenual anterior cingulate cortex, the SZ group presented increased rsFC from the vAIC and dAIC to the right caudate. Compared with the BD group, the SZ group showed significantly increased rsFC from the vAIC and dAIC to the left middle frontal gyrus. Conclusions: The shared AIC rsFC abnormalities in both BD and SZ support the importance of the AIC in the common pathophysiology of BD and SZ. There were also disorder-specific features of AIC rsFC, which might implicate potential avenues for differentiating during the early stages.